Neoclassical transport in toroidal plasmas with nonaxisymmetric flux surfaces. (May 2015) - Belli, E A; Candy, J
Abstract The capability to treat nonaxisymmetric flux surface geometry has been added to the drift-kinetic code NEO (Belli and Candy 2008 Plasma Phys. Control. Fusion50 095010). Geometric quantities (i.e. metric elements) are supplied by a recently-developed local 3D equilibrium solver, allowing neoclassical transport coefficients to be systematically computed while varying the 3D plasma shape in a simple and intuitive manner. Code verification is accomplished via detailed comparison with 3D Pfirsch–Schlüter theory. A discussion of the various collisionality regimes associated with 3D transport is given, with an emphasis on non-ambipolar particle flux, neoclassical toroidal viscosity, energy flux and bootstrap current. Finally, we compute the transport in the presence of ripple-type perturbations in a DIII-D-like H-mode edge plasma.